Pengaruh Islamic Leadership Dan Budaya Religiusitas Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Karyawan Sebagai Variabel Intervening Pada PT. Bank Syariah Indonesia Kantor Area Malang - Aktsal Shira Sabilillah; Mohammad Rizal; Andi Normaladewi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of association, fashion trends, and financial literacy on consumptive lifestyles. This research method uses quantitative methods. With the data collection technique by distributing questionnaires to students of the 2019 class of the Faculty of Economics and Business UNISMA. The results of this study used SPSS. The results of this study indicate that: social influence has a positive effect on consumptive lifestyles. fashion trends have a positive effect on consumptive lifestyles financial literacy has a positive effect on consumptive lifestyles. The significance value of 0.000 is less than 0.05, meaning that the variables of social influence, fashion trends, and financial literacy simultaneously influence consumptive lifestyles. Keywords: Influence of Association, Fashion Trend, Financial Literacy, Consumptive Lifestyle.